1982
DOI: 10.1093/ajcn/35.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in cervical dysplasia associated with folic acid therapy in users of oral contraceptives

Abstract: Forty-seven young women with mild or moderate dysplasia of the uterine cervix (cervical intraepithelial neoplasia) diagnosed by cervical smears, received oral supplements of folic acid, 10 mg, or a placebo (ascorbic acid, 10 mg) daily for 3 months under double-blind conditions. All had used a combination-type oral contraceptive agent for at least 6 months and continued it while returning monthly for follow-up examinations. All smears and a biopsy obtained at the end of the trial period were classified by a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Premalignant dysplasia of cervical, bronchial and colonic epithelial cells could be reversed by folate supplementation implying that folate deficiency may have a causal role in the process (Lashner et al, 1989;Rosenberg and Mason, 1989;Butterworth et al, 1991). Elucidation of the molecular mechanisms underlying folate deficiency and predisposition to cancer is, therefore, of critical importance for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Premalignant dysplasia of cervical, bronchial and colonic epithelial cells could be reversed by folate supplementation implying that folate deficiency may have a causal role in the process (Lashner et al, 1989;Rosenberg and Mason, 1989;Butterworth et al, 1991). Elucidation of the molecular mechanisms underlying folate deficiency and predisposition to cancer is, therefore, of critical importance for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent associations between low serum levels, low tissue concentrations, and/or low dietary intake of vitamin A (5), ß-carotene (6)(7)(8), folie acid (9)(10)(11), vitamin C (5,9,12), and vitamin E (13) and an increased prevalence of cervical intraepithelial neoplasia (CIN) and/or invasive cervical cancer have been observed.…”
mentioning
confidence: 92%
“…In vivo and in vitro studies have reported that low-folate conditions increase chromosomal breakage, micronucleus formation, defects in chromosome condensation (15,17,18), metastatic potential of cultured murine melanoma cells (19), and expression of chromosomal fragile sites (20,21). Evidence indicates that certain in vivo human cell populations may be folate-deficient even when blood folate values are normal and that cellular dysplasia associated with low-folate status in cervix and lung can be reversed by folate administration (22)(23)(24).…”
mentioning
confidence: 99%